2005
DOI: 10.1152/ajpgi.00273.2004
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4- and -13-induced hypercontractility of human intestinal muscle cells-implication for motility changes in Crohn's disease

Abstract: . Interleukin-4-and -13-induced hypercontractility of human intestinal muscle cells-implication for motility changes in Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…Inflammation is associated with structural and functional changes in the contractile apparatus of gut that leads to altered motor function (6,43). Hypercontractility, especially of longitudinal smooth muscle, has been reported in IBD patients, especially Crohn's patients, and is a characteristic of a variety of models of gut inflammation (2,3,20,27,33,43,51). Similarly, hypercontractility of airway smooth muscle is also a hallmark of lung inflammation and BDNF upregulation during airway inflammation has been shown to mediate this hypercontractility (1,28,40,49,57).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is associated with structural and functional changes in the contractile apparatus of gut that leads to altered motor function (6,43). Hypercontractility, especially of longitudinal smooth muscle, has been reported in IBD patients, especially Crohn's patients, and is a characteristic of a variety of models of gut inflammation (2,3,20,27,33,43,51). Similarly, hypercontractility of airway smooth muscle is also a hallmark of lung inflammation and BDNF upregulation during airway inflammation has been shown to mediate this hypercontractility (1,28,40,49,57).…”
Section: Discussionmentioning
confidence: 99%
“…These differences in contractile responses may be due to differences in cytokine profiles. Reports from the Collins group (Akiho et al, 2002;Akiho et al, 2005a;Akiho et al, 2005b) have suggested that nematode-induced hypercontractility is mediated by an increase in prostaglandin E2 (PGE2) levels after induction of the expression of Th2 cytokines such as interleukin (IL)-4 and IL-13.…”
Section: Motility Disorders In Intestinal Inflammationmentioning
confidence: 99%
“…These differences in contractile responses may be due to differences in cytokine profiles. Reports from the Collins group (Akiho et al, 2002;Akiho et al, 2005a;Akiho et al, 2005b) have suggested that nematode-induced hypercontractility is mediated by an increase in prostaglandin E2 (PGE2) levels after induction of the expression of Th2 cytokines such as interleukin (IL)-4 and IL-13.On the other hand, reports suggest that TNBS-induced gut inflammation is mediated mainly by Th1 cytokines such as IL-1β, tumor necrosis factor-α (TNF-α) and IL-12 (Neurath et al, 1995; Kinoshita et al, 2006; Kiyosue et al, 2006;Ohama et al, 2007b). In this review, we focused on the molecular mechanisms that are responsible for the decreased motility of the inflamed intestine.…”
mentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-␣ can attenuate carbachol (CCh)-induced contraction in colonic inflammation induced by 2,4,6-trinitrobenzenesulfonic acid (TNBS) in C57BL/6 mice (Ohama et al, 2007). Alternatively, it was reported that incubation of human cultured smooth muscle cells with T H 2 cytokines, interleukin (IL)-4 or IL-13, enhanced CCh-induced contraction via activation of signal transducer and activator of transcription 6 (STAT6) (Akiho et al, 2005b). Collectively, the T H 1 and T H 2 immune responses are associated with hypocontractility and hypercontractility of inflamed intestinal smooth muscle, respectively.…”
mentioning
confidence: 99%